Hybridization potential Aegilops sp. / durum wheat: which interest for the genetic breeding of the drought tolerance? - Fethia ZADRI; Kamel KELLOU; Adra MOUELLEF; Hadjer BOUANIKA; Ryma BOULDJEDJ; Chafika ZAHRAOUI; Abdelhamid DJEKOUN; Nadia YKHLEF (Acta Agriculturae Slovenica)
To study their hybridization potential, two species of the genus Aegilops (Aegilops geniculata Roth; Aegilops triuncialis L.) and two durum wheat (Triticum durum Desf.) varieties (‘Oued Zenati’ and ‘Hoggar’) were crossed, where Aegilops was the female parent. The four cross combinations were tested during five years in order to release the genitors having the most affinity for obtaining interspecific hybrids. The parents were also characterized for their drought stress tolerance during the crossing period. The results confirm the tolerance of Aegilops sp. and adaptation of the durum wheat varieties to climatic conditions governing the Algerian cereal zones. 81 hybrids F1 were obtained. Differences in hybridization affinity between the parents were very remarkable. The combination of parents Aegilops geniculata/’ Oued Zenati’ has produced the highest number of hybrids (54 or a rate of 5.23 %), followed by Aegilops triuncialis/’Oued Zenati’ (18 hybrids or a rate of 3.88 %). The crossing of the two Aegilops species with the Hoggar variety produced a small number of hybrids. Among the advantages of this crossing, the obtaining of hybrids in caryopsis without resorting to the embryos rescue. Hybrid seedlings expressed a maternal cytoplasmic heredity. However, no adult plant could have been regenerated.